Ni-based alloy catalysts for cost-effective hydrogen production from ammonia decomposition - Yeongjun Yoon; Yunseo Choi; Yonggyun Bae; Jongsup Hong; Kyeounghak Kim (Applied Surface Science Advances)
Due to its high hydrogen storage capacity and established infrastructure, ammonia (NH3) decomposition has been extensively investigated as a clean hydrogen production process. However, hydrogen production via ammonia decomposition faces various challenges. Although ruthenium (Ru) catalysts exhibit the highest activity for ammonia decomposition, their scarcity and high cost hinder commercial application. Consequently, nickel (Ni) catalysts have emerged as a potential alternative, owing to their cost-effectiveness and high activity. To further optimize Ni catalysts, developing Ni-based alloy catalysts with other metals is a promising solution. Herein, density functional theory (DFT) calculations are performed to elucidate the catalytic activity of 3d transition metals (Ni, Co, Cu, and Fe) and their promising alloys. The key reaction steps of overall ammonia decomposition are NHx‒H bond scission (NHx*→NHx-1*+H*) and N + N recombination (N*+N*→N2*). In particular, nitrogen adsorption energy (Ead(N)) serves as a descriptor for predicting the activation energies of key elementary steps, revealing a volcano-like relationship between experimental catalytic activity and DFT-calculated Ead(N). Additionally, we discover a strong correlation between d-band filling (fd) and Ead(N), establishing fd as an effective descriptor that not only predicts Ead(N) but also the catalytic activity of NH3 decomposition. Our descriptor-based design principle identifies Ni0.64Fe0.36 as a potentially effective and cost-efficient candidate for hydrogen production from ammonia, with experimental data demonstrating its superior performance compared to pure Ni. These findings offer valuable insights into the development of efficient, economically viable transition metal-based catalysts for hydrogen production through ammonia decomposition.